1993
DOI: 10.1111/j.1475-1313.1993.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral astigmatic asymmetry and angle alpha

Abstract: The association between peripheral astigmatic asymmetry and angle alpha was tested in the present study. Measurements were made in 34 eyes. Peripheral astigmatism was measured over the horizontal meridian using a Zeiss (Jena) Hartinger coincidence optometer and a Canon R-1 autorefractometer. Curves were fitted to the measured data of each eye and the minima determined by differentiation. Angle alpha was estimated by alignment of Purkinje images I (anterior cornea) and IV (posterior crystalline lens). Periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 9 publications
7
32
0
Order By: Relevance
“…In the literature it is reported that peripheral astigmatism is minimum about one point of the nasal retina. 18,19 Our results seem to agree with this finding, since we find a double minimum in the astigmatism. Nevertheless, it has also been reported that in primates the fovea appears at the point where the best image is formed.…”
Section: Discussionsupporting
confidence: 81%
“…In the literature it is reported that peripheral astigmatism is minimum about one point of the nasal retina. 18,19 Our results seem to agree with this finding, since we find a double minimum in the astigmatism. Nevertheless, it has also been reported that in primates the fovea appears at the point where the best image is formed.…”
Section: Discussionsupporting
confidence: 81%
“…It is possible that the flatter peripheral cornea has relatively more influence on refraction in patients with large eyes and extreme myopia; for instance, if the corneal apex is relatively farther from the optical axis in myopic eyes with a greater angle alpha. 9 This would lead to a more hyperopic outcome than predicted if biometry corneal curvature readings relate to stronger, more central areas of the cornea. 10 Another study looking specifically at errors in corneal curvature readings in high myopia, however, still found that corneal curvature readings were less significant than axial length measurements in producing biometry errors.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that though selective individual ocular component modeling yielded the required levels of myopia and their respective models, all the parameters were found to be within the range of normal values of the population. [53][54][55][56][57][58][59][60] In this experiment, we considered the retinal surface to be a rotationally symmetric aspheric surface for all the myopic models and assumed it to be invariable over the range and types of myopic prescription chosen. The rationale was to limit the degrees of freedom so as to keep the experiment simpler.…”
Section: Discussionmentioning
confidence: 99%